Synergistic Effect of Cu Single Atoms and Au–Cu Alloy Nanoparticles on TiO2 for Efficient CO2 Photoreduction - Yu, Yangyang; Dong, Xing’an; Chen, Peng; Geng, Qin; Wang, Hong; Li, Jieyuan; Zhou, Ying; Dong, Fan (ACS nano, 2021)
The synergy between metal alloy nanoparticles (NPs) and single atoms (SAs) should maximize the catalytic activity. However, there are no relevant reports on photocatalytic CO2 reduction via utilizing the synergy between SAs and alloy NPs. Herein, we developed a facile photodeposition method to coload the Cu SAs and Au–Cu alloy NPs on TiO2 for the photocatalytic synthesis of solar fuels with CO2 and H2O. The optimized photocatalyst achieved record-high performance with formation rates of 3578.9 for CH4 and 369.8 μmol g–1 h–1 for C2H4, making it significantly more realistic to implement sunlight-driven synthesis of value-added solar fuels. The combined in situ FT-IR spectra and DFT calculations revealed the molecular mechanisms of photocatalytic CO2 reduction and C–C coupling to form C2H4. We proposed that the synergistic function of Cu SAs and Au–Cu alloy NPs could enhance the adsorption activation of CO2 and H2O and lower the overall activation energy barrier (including the rate-determining step) for the CH4 and C2H4 formation. These factors all enable highly efficient and stable production of solar fuels of CH4 and C2H4. The concept of synergistic SAs and metal alloys cocatalysts can be extended to other systems, thus contributing to the development of more effective cocatalysts.